Unstable tilting motion of flexibly supported gas bearing bushings. (1st January 2022) - Bättig, Philipp; Schiffmann, Jürg
Highlights: Experimental proof of unstable bushing tilting motion of gas lubricated bearings. Unstable motion initiated by cross-coupled titling bearing impedance. Bushing tilting modes and instability onset can be predicted by reduced order model. Bushing inertia and flexible support impedance are key to control instability. Tilting Eigenfrequency higher than half the max rotor speed to prevent instability. Abstract: This paper presents measurements of the motion amplitudes from flexibly supported Herringbone Grooved Journal Bearing bushings. Measurements taken in four locations on the flexibly supported bearing bushing enable the distinction between the radial and the tilting motion, which allowed to identify an unstable bearing bushing tilting mode. The bushing tilting motion instability can be attributed to the cross-coupled tilting impedance of the gas bearing and its occurrence is characterized by the appearance of a sub-synchronous vibration at the speed of instability onset. The comparison between experimentally obtained data and the prediction of a two degrees of freedom dynamic model that includes the flexible support characteristics, the bushing transverse inertia as well as the gas bearing tilting impedance suggests an excellent agreement on both the Eigenfrequency and the rotor speed of instability onset. Furthermore, the effect of the flexible support tilting stiffness and bearing bushing transverse moment of inertia on the critical bushing tilting speed and onset of tilting instability has been investigated, which led to a design guideline to avoid the onset of an unstable bush tilting mode. In addition, experimental data gathered after the introduction of damping in the flexible support of the bearing bushing suggests a significant increase of the onset speed of the unstable bearing bushing tilting mode.